(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study aimed to document the diversity, distribution, and feeding habits of insect pests associated with the crop. a total of 17 insect species from seven orders (coleoptera, hemiptera, diptera, hymenoptera, lepidoptera, orthoptera, and thysanoptera) were recorded, with coleoptera (41.18%) and hemiptera (29.41%) being the most dominant. the family chrysomelidae had the highest representation with four species, while other families had one species each. The pests were categorized by feeding behavior: defoliators (11 species, 64.71%), sap-suckers (5 species, 29.41%), and tissue feeders (1 species, 5.88%). chewing insects, especially coleopteran defoliators, were the main cause of crop damage, while sap-sucking pests caused indirect damage through nutrient depletion and pathogen transmission. These findings provide a baseline for understanding pest dynamics, which is essential for developing effective integrated pest management (ipm) strategies to reduce crop losses while highlighting the need for regular monitoring and management of both defoliators and sap-sucking pests.